PETA KENDALI-P UNTUK CACAT PRODUKSI KAIN DI PT RANJANG GAJAH TEKSTIL MENGGUNAKAN PENDEKATAN CONTROL CHARTS - -, Noeryanti (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
The aim of this study was to know the a mount of production prosess ability at PT Ranjang Gajah Tekstil, by data of defect production. The observation based on secondary data, whereas the analysis approach used was p-control graphic with control chart.By using p-control graphic, it seemed that there was observation out of control caused by uncontrol production. Through some improvements, the result which was abtained showed that production process ability caused by lusi movement decreasing 0,163%, pakan movement decreasing 0,259%, ngapuk decreasing 0,054% , and sobek decreasing 0,041%.It was found that the special cause of defect data of lusi movement were, one the 21st observation cause of rusty sisir the 33rd, 34th adn 37th ones cause of broken fork gird. For pakan movement defects found that on the 1st, 2nd, 3rd, 16th, 17th, and 52nd ones caused by loose shuttle, on the 4th and 5th ones cause of less good shuttle replacement, and on the 6th one cause of sisir kecak. Therefore the result of this study used by the company in order to do improvements and be able to observe process ability continually in order to be stable.